ICBP90 Regulates MIF Expression, Glucocorticoid Sensitivity, and Apoptosis at the MIF Immune Susceptibility Locus. Issue 10 (3rd September 2021) - Yao, Jie; Leng, Lin; Fu, Weiling; Li, Jia; Bronner, Christian; Bucala, Richard
Abstract : Objective: Macrophage migration inhibitory factor (MIF) is an inflammatory and neurorendocrine mediator that counterregulates glucocorticoid immunosuppression. MIF polymorphisms, which comprise a variant promoter microsatellite (−794 CATT5–8 ), are linked genetically to autoimmune disease severity and to glucocorticoid resistance. While invasive stimuli increase MIF expression, MIF also is up‐regulated by glucocorticoids, which serve as a physiologic regulator of inflammatory responses. This study was undertaken to define interactions between the MIF promoter, the glucocorticoid receptor (GR), and the transcription factor inverted CCAAT box binding protein 90 kd (ICBP90) (also referred to as UHRF1), which binds to the promoter in a −794 CATT5–8 length–dependent manner, to regulate MIF transcription. Methods: Interactions of ICBP90, GR, and activator protein 1 (AP‐1) with MIF −794 CATT5–8 promoter constructs were assessed by coimmunoprecipitation, Western blotting, and genetic knockdown. Nuclear colocalization studies were performed using anti–transcription factor antibodies and confocal microscopy of glucocorticoid‐treated cells. MIF transcription was studied in CEM‐C7 T cells, and the impact of the MIF −794 CATT5–8 microsatellite variation confirmed in peripheral blood T cells and in rheumatoid synovial fibroblasts of defined MIF genotype. Functional interactions were quantified by apoptosis and apoptotic signaling in high‐ and low‐genotypic MIF –expressing human cells. Results: We defined functional interactions between the transcription factors ICBP90, the GR, and AP‐1 that up‐regulated MIF transcription in a −794 CATT5–8 length–dependent manner. Experimental reduction of ICBP90, GR, or AP‐1 decreased MIF expression and increased glucocorticoid sensitivity, leading to enhanced apoptosis in T lymphocytes and in rheumatoid synovial fibroblasts. Conclusion: These findings suggest a mechanism for genetic variation of glucocorticoid‐regulated MIF transcription, with implications for autoimmune disease severity and glucocorticoid responsiveness.